2021
DOI: 10.1155/2021/6645124
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical Model Experiment Study on Deformation and Failure Mechanism of the Mountain Tunnel in Layered Jointed Rock Mass

Abstract: The Minxian tunnel is a key engineering of the Weiyuan-Wudu expressway that is excavated in layered jointed carbonaceous slate rock mass. During the construction process, the surrounding rocks of the tunnel encountered serious large deformations and failure, which brought about great difficulties to the safety and cost of the tunnel. In order to study the deformation and failure mechanism of the surrounding rocks, a physical model test was conducted, and integrated methods including strain gauges, a digital ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…After substituting the partial derivative of Equation (1) into Equation (10), the plastic shear strain in each principal direction can be obtained: 4 Geofluids…”
Section: Geofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…After substituting the partial derivative of Equation (1) into Equation (10), the plastic shear strain in each principal direction can be obtained: 4 Geofluids…”
Section: Geofluidsmentioning
confidence: 99%
“…In recent years, extensive research has been conducted on the deformation and failure characteristics of layered rock mass [1][2][3][4][5][6][7]. Xia et al [1] studied the bearing deformation and failure process of layered rock mass through a model test and revealed the eccentric pressure failure phenomenon of surrounding rock.…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that any tunnel section is parallel to the isotropic plane, the analytical solution for stress and displacement around any tunnel has been derived [28][29] . There is also comprehensive research on the stress distribution, deformation, and failure characteristics of surrounding rock in layered rock masses [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] comprehensively examined the effects of roadway shape and fault dip angle on roadway damage, studying the initiation position and propagation path of cracks under the respective influences. Guo et al [16] analyzed the deformation evolution process of layered jointed roadway surrounding rock models and found that the distribution of stress concentration zones in the surrounding rock is highly uneven due to the unique characteristics of layered joint structures.…”
Section: Introductionmentioning
confidence: 99%